Rekonstrukcja malowideł jako forma przywrócenia harmonii wnętrza na przykładzie malowideł stropowych w kościele pw. Niepokalanego Serca Najświętszej Marii Panny w Okartowie - Stachera, Jacek (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2011)
In conservation-restoration practice we often face the dilemma whether to reconstruct or not. Many people are against it, as a violation of the preserved, historic look of the work of art, justified by passing time and occurring alterations. There are, however monuments, in which reconstruction is advisable, because it allows to bring back the original, whole conception of the artist. As an example justifying this thesis may serve the reconstruction of painted decoration on ceilings of the galleries in the church of Immaculate Heart of the Blessed Virgin Mary in Okartowo. This paper, after a short presentation of the church history discusses the course of carried out conservation-restoration works and then justifies the necessity of reconstructing missing fragments.